2013
DOI: 10.1136/bmjopen-2013-003971
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic workup for fever of unknown origin: a multicenter collaborative retrospective study

Abstract: ObjectiveFever of unknown origin (FUO) can be caused by many diseases, and varies depending on region and time period. Research on FUO in Japan has been limited to single medical institution or region, and no nationwide study has been conducted. We identified diseases that should be considered and useful diagnostic testing in patients with FUO.DesignA nationwide retrospective study.Setting17 hospitals affiliated with the Japanese Society of Hospital General Medicine.ParticipantsThis study included patients ≥18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 20 publications
(17 reference statements)
5
55
3
1
Order By: Relevance
“…[15][16][17][18] In several recent studies no cause could be found in a large proportion of patients (Table 1). 3,5,[19][20][21] Lower incidences of specifi c infections, such as tuberculosis and brucellosis, and differences in availability of modern imaging techniques, such as CT, MRI and FDG-PET/CT, may among others cause these differences.…”
Section: Defi Nition and Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] In several recent studies no cause could be found in a large proportion of patients (Table 1). 3,5,[19][20][21] Lower incidences of specifi c infections, such as tuberculosis and brucellosis, and differences in availability of modern imaging techniques, such as CT, MRI and FDG-PET/CT, may among others cause these differences.…”
Section: Defi Nition and Causesmentioning
confidence: 99%
“…Measurement of cryoglobulins and fundoscopic examination should be performed in an early stage, because of the frequent absence of typical symptoms in diseases that can be found by these investigations and their relatively low cost. 4 When these tests do not lead to the fi nal diagnosis, one should proceed to whole body imaging, 6 preferably with 18 FDG-PET/CT. 23 …”
Section: Investigating Fuomentioning
confidence: 99%
“…Use of 18 FDG PET and PET CT has been documented in several studies to differentiate various etiologies without resorting to invasive techniques as employed by our centres when the first line investigations fail to give a diagnosis. [19,20] PET CT had contributed to 25%-69% of final diagnosis of FUO especially focal abdominal/ thoracic infections, osteomyelitis, large vessel vasculitis, sarcoidosis and malignancies. [20] Absence of PET CT, electron microscopy and viral marker probes can be considered a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplasiát, infekciót mindig ki kell zárni, előfordul, hogy belgyógyászati vagy neurológiai betegség jelenik meg hasonló formában. Ismeretlen eredetű láz (FUO) egy részében is PMR igazolható [34]. Sok esetben társul GCA, ilyenkor annak ischaemiás differenciáldiagnosztikáját is szem előtt kell tartani [4].…”
Section: Differenciáldiagnózisunclassified